2013
DOI: 10.1371/journal.pone.0054167
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of High Aedes aegypti Oviposition Activity in Northwestern Argentina

Abstract: BackgroundIn Argentina, dengue has affected mainly the Northern provinces, including Salta. The objective of this study was to analyze the spatial patterns of high Aedes aegypti oviposition activity in San Ramón de la Nueva Orán, northwestern Argentina. The location of clusters as hot spot areas should help control programs to identify priority areas and allocate their resources more effectively.MethodologyOviposition activity was detected in Orán City (Salta province) using ovitraps, weekly replaced (October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…No significant differences ( P = 0.67) were detected either regarding oviposition activity sectors based on Estallo et al . (2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant differences ( P = 0.67) were detected either regarding oviposition activity sectors based on Estallo et al . (2013).…”
Section: Resultsmentioning
confidence: 99%
“…Estallo et al . (2013) analyzed the spatial patterns of Ae. aegypti oviposition activity and identified hot spot areas in central and southern regions of Orán city.…”
Section: Methodsmentioning
confidence: 99%
“…Aedes (Stegomyia) aegypti is well known as the main vector of dengue [ 1 ], widely distributed from tropical to subtropical areas of the world [ 2 ]. In Argentina, it reaches central temperate regions of the country [ 3 5 ], although eggs have also been found in the Patagonia region (Neuquén Province) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…aegypti oviposition activity has also been developed for Oran, which enabled a predictive map with areas of maximum probability of Ae . aegypti oviposition activity and high risk areas of transmission [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies in the subtropical northwest region of Argentina revealed a year-round vector population in areas with an annual mean temperature around 20°C. A low number of eggs was recorded during the winter season, and peak in oviposition was detected during summer months (December to March in the southern hemisphere) [21–24]. Studies from the temperate central areas, like Buenos Aires [2529] and Córdoba provinces [30–32], found that oviposition discontinued during the winter months due to low temperatures (below 17°C), with a peak in Ae.…”
Section: Introductionmentioning
confidence: 99%